Fruit and seed of Eriotheca dolichopoda (Malvaceae) revealed after 45 years: Emended description, typification, new records, and conservation status of a poorly known Atlantic Forest species - Carvalho-Sobrinho, Jefferson; Mota, Aline C.; Alverson, William S.; Dorr, Laurence J. (Phytotaxa, 2024)
Eriotheca dolichopoda (Malvaceae) is a tree species endemic to Atlantic Forest in the state of Bahia, northeastern Brazil. Its fruit and seed were unknown and had not been illustrated. Herein we describe and illustrate for the first time the fruit and seed of E. dolichopoda, provide an emended morphological description, designate a lectotype, and designate an epitype to permit a precise application of the name. We also discuss morphological variation in E. dolichopoda and its affinities with similar species. Finally, we use fieldwork and herbarium data to provide a distribution map and an updated conservation assessment of E. dolichopoda based on IUCN criteria.